Arrayed waveguide gratings based on perfluorocyclobutane polymers for CWDM applications - Jia Jiang; Callender, C.L.; Blanchetiere, C.; Noad, J.P.; Shengrong Chen; Ballato, J.; Smith, D.W. (IEEE photonics technology letters, 2006)
Compact wavelength-division multiplexers based on arrayed waveguide grating structures have been designed and fabricated for short-haul communication network applications using low-loss perfluorocyclobutane-containing polymers. The devices exhibit high thermal stability and low on-chip losses. The average on-chip loss was <6 dB, including the fiber-to-chip coupling loss. The output uniformity across five channels was typically /spl plusmn/0.5 dB, and the thermal sensitivity of the central wavelength was 0.045nm//spl deg/C. Optimization of devices through material properties and fabrication process parameters is discussed.